Effect of probiotics on clinical and immune parameters in enthesitis‐related arthritis category of juvenile idiopathic arthritis. (19th August 2016) - Shukla, A.; Gaur, P.; Aggarwal, A.
Summary: Gut microflora and dysbiosis as an environmental factor has been linked to the pathogenesis of enthesitis‐related arthritis (JIA‐ERA); thus, we performed a proof‐of‐concept study of probiotics to modulate the gut‐flora and study the effects on immune and clinical parameters of children having JIA‐ERA. Forty‐six children with active JIA‐ERA were randomized to placebo or probiotic therapy along with non‐steroidal anti‐inflammatory drugs (NSAIDs) for 12 weeks. Patients were assessed using a six‐point composite disease activity index (mJSpADA) based on morning stiffness, joint count, enthesitis count, sacroiliitis/inflammatory back pain, uveitis and erythrocyte sedimentation rate/C‐reactive protein (ESR/CRP). Frequencies of T helper type 1 (Th1), Th2, Th17 and regulatory T cells in blood were measured using flow cytometry. Serum cytokines interferon (IFN)‐γ, interleukin (IL)−4, IL‐17, IL‐10, tumour necrosis factor (TNF)‐α and IL‐6 were measured by cytokine bead array using flow cytometer. The average age of 46 children (44 boys) was 15 ± 2.5 years and duration of disease was 3.5 ± 3 years. There was no significant difference in improvement in mJSpADA between the two groups ( P = 0·16). Serum IL‐6 levels showed a decrease ( P < 0·05) in the probiotic‐group. Th2 cell frequency ( P < 0·05) and serum IL‐10 levels ( P < 0·01) showed an increase in the placebo group, but again the probiotic use did not show a significant change in immune parameters when compared to the placebo. Adverse effects among the probiotic and placebo groups were diarrhea (36 versus 45%), abdominal pain (9 versus 20%), minor infections (4·5 versus 20%) and flatulence (23 versus 15%), respectively. Thus, we can conclude that probiotic therapy in JIA‐ERA children is well tolerated, but failed to show any significant immune or clinical effects over NSAID therapy.